2018
DOI: 10.1097/iae.0000000000001748
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Subretinal Hyperreflective Material in Neovascular Age-Related Macular Degeneration Treated With Bevacizumab

Abstract: This study supports the use of SHRM as a prognostic biomarker when interpreting optical coherence tomography in neovascular age-related macular degeneration. Baseline parameters predicting poorer vision 1 year after intravitreal bevacizumab treatment were as follows: presence of central SHRM, well-defined SHRM borders, intraretinal fluid, and thicker SHRM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 19 publications
2
37
0
2
Order By: Relevance
“…Several studies corroborated these findings and showed that the clinical course of HRM influences visual outcome of anti-VEGF therapy. We and others have shown that eyes with undefined HRM or no HRM prior to treatment are less likely to progress to fibrosis and have better visual outcomes as compared to eyes with defined HRM or extensive HRM at baseline [23,[35][36][37]. Moreover, a decrease in HRM thickness and volume after treatment correlates with an improvement in visual acuity 12 months after initiation of treatment [38].…”
Section: Hrm As a Predictive And Prognostic Biomarkermentioning
confidence: 87%
See 1 more Smart Citation
“…Several studies corroborated these findings and showed that the clinical course of HRM influences visual outcome of anti-VEGF therapy. We and others have shown that eyes with undefined HRM or no HRM prior to treatment are less likely to progress to fibrosis and have better visual outcomes as compared to eyes with defined HRM or extensive HRM at baseline [23,[35][36][37]. Moreover, a decrease in HRM thickness and volume after treatment correlates with an improvement in visual acuity 12 months after initiation of treatment [38].…”
Section: Hrm As a Predictive And Prognostic Biomarkermentioning
confidence: 87%
“…Indeed eyes presenting with well-defined HRM have the highest risk of scarring, whereas those with undefined HRM have a lower risk [15]. Other features of HRM such as well-defined borders prior to initiation of therapy, high reflectivity, a zone of separation between HRM and the outer retina, a layered appearance, subretinal hyperreflective spots, thicker and wider HRM have been shown to correlate with poor visual outcome [23,[35][36][37].…”
Section: Hrm As a Predictive And Prognostic Biomarkermentioning
confidence: 99%
“…Zwykle istotne zmniejszanie się ilości płynu podsiatkówkowego stwierdza się po pierwszych 3 comiesięcznych iniekcjach. Niemniej jednak nie stwierdzono by utrzymywanie się pewnych jego resztkowych ilości miało negatywny wpływ na widzenie [41]. Oczywiście powiększanie się obszaru występowania płynu lub zwiększenia jego ilości podczas wizyt kontrolnych sugeruje wzrost aktywności CNV.…”
Section: Płyn Podsiatkówkowyunclassified
“…F ibrosis is one of the most important threats to vision in neovascular age-related macular degeneration (AMD) and, despite optimal treatment, develops in almost half of all eyes after 2 years. [1][2][3][4] Subretinal hyperreflective material (SHRM) on optical coherence tomography (OCT) has been identified as a risk factor for fibrosis and may be observed in up to three quarters of eyes with treatment-naïve choroidal neovascularization (CNV) secondary to AMD. [1][2][3][4][5][6] SHRM has had a negative impact on best-corrected visual acuity (BCVA) and eyes showing reduction of SHRM with anti-VEGF treatment have a better visual prognosis than eyes with SHRM resistant to treatment.…”
mentioning
confidence: 99%
“…[1][2][3][4] Subretinal hyperreflective material (SHRM) on optical coherence tomography (OCT) has been identified as a risk factor for fibrosis and may be observed in up to three quarters of eyes with treatment-naïve choroidal neovascularization (CNV) secondary to AMD. [1][2][3][4][5][6] SHRM has had a negative impact on best-corrected visual acuity (BCVA) and eyes showing reduction of SHRM with anti-VEGF treatment have a better visual prognosis than eyes with SHRM resistant to treatment. 1,3,4,7 One hypothesis states that anti-VEGF therapy may cause a decrease in vascular components and an increase in fibrous components, thus promoting the transition from angiogenesis to fibrosis, a reaction termed the angiofibrotic switch.…”
mentioning
confidence: 99%